Clinical and Ultrasonic Study for Detection of Pregnancy in Iraqi Buffaloes - AL-Sariy, S. M.; AL-Yasiri E. A.; AL-Hamedawi T. M. (The Iraqi Journal of Veterinary Medicine, 2020)
The present study was conducted on 10 Iraqi pregnant buffaloes aged between 3-6 years at Al-Qasim district- Babylon province, Iraq from December 2018 to December 2019. Those animals diagnosed by rectal palpation and ultrasonography technique to estimate the reproduction status. The results of this study reported wandering of ovum in 10% of animals (1/10). While ultrasonography characterized by increasing placentomes measurement gradually with development of gestation, and the placentomes recorded 8.32±2.46 mm, 13.27±3.25 mm, 18.37±5.34 mm, 23.25±8.63 mm and 28.2±6.87 mm in the 2nd , 3rd, 4th, 5th and 6th month, respectively. Also the total size was recorded by the crown rump length (CRL), which was 0.77±0.05 cm, 5.81±2.54 cm and 14.09±0.73 cm in the 1st, 2nd, and 3rd month, respectively. The heart beat and embryonic vesicle during the 1st and 2nd month were detectable by ultrasonography. In conclusions in the present study, rectal palpation and ultrasonography technique represented one of the most important methods to estimate the gestation period in different stages.